The Combination of Balanced Nutrition Menu in Controlling Undernutrition in Toddlers Through Supplementary Feeding in Community Health Center Enok, Indragiri Hilir Regency - Riski Novera Yenita; Rifa Yanti; Dilgu Meri (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Undernutrition among children under five is a serious challenge in achieving Sustainable Development Goals (SDGs) Goal 2. In the working area of UPT Puskesmas Enok, especially Rantau Panjang Village, the prevalence of undernutrition still requires innovative interventions. Supplementary feeding (PMT) based on local food with a balanced nutritional menu is expected to be a sustainable solution compared to manufactured processed products. The purpose of the study was to analyze the effectiveness of providing PMT with a combination of a balanced nutrition menu in increasing the body weight of undernourished toddlers in Rantau Panjang Village. Type of quantitative research with a quasi-experiment one-group pretest-posttest design. The research was conducted in Rantau Panjang Village. The population of this study was all toddlers diagnosed with undernutrition in the work area of Community Health Center Rantau Panjang, 42 toddlers. The sampling technique was purposive sampling, obtaining 7 toddlers with an age range of 12-59 months. The results showed that the average body weight of toddlers before the intervention was 9.77 kg (SD = 2.4) and after the intervention increased to 10.38 kg (SD = 2.5), with an average increase of 0.6 kg. Statistical tests showed a p-value of 0.000 (p < 0.05), which means that there is a significant effect of providing a balanced nutrition menu PMT on toddler weight. Puskesmas are advised to adopt this balanced nutrition menu model as a standard operating procedure in handling underweight children. The Rantau Panjang Village Government is expected to integrate the village fund budget to support the sustainability of this program. Keywords: Balanced Nutrition Menu, Toddler, Undernutrition, Supplementary Feeding.